The Effects of Viral Lato-Lato Games on Elementary School Students - Dinah Nadhifah; Fadiah Adlina; Novita Sari Nasution (Journal of Contemporary Islamic Primary Education, 2023)
This study aims to analyze the impact of the viral game in the form of Lato-lato and its impact on elementary age children. The descriptive-qualitative research method was used in this study which aims to provide an overview and present information about something according to the conditions at that time. Data collection in this study was through interviews and observations around the Matauli Pandan housing complex. The results showed that children who play lato-lato tend to be more active in interacting and socializing, considering that this game is more fun when played together. In addition, with increasing social interaction, children also reduce the intensity of children's use and dependence on gadgets. Therefore, if it is still under good supervision from parents, this game will help children to improve their motoric and cognitive abilities, as well as their social skills.